Application of Technological Pedagogical Content Knowledge (TPACK) learning by al-Qur'an hadith teachers to the learning outcomes of al-Qur'an hadith at MAS DDI Tellu Limpoe, Sidrap Regency - Suriana; Ahdar; Hamsa; Ambo Dalle; Usman (Universitas Muhammadiyah Palu, 2024)
This research aims to determine the results of implementing the Technological Pedagogical Content Knowledge (TPACK) learning model on student learning outcomes, especially in the Al-Qur'an Hadith subject at MAS DDI Tellu Limpoe, Sidrap Regency. The research method used in this research is a quantitative experiment, where this method is a research method used to examine certain populations and samples. The type of research used in this research is a quasi-experimental design, where the groups are not chosen randomly but use two groups, namely the experimental group, namely the group that was given scientific Technological Pedagogical Content Knowledge (TPACK) treatment, and the control group, namely the group that was treated with conventional learning. . The class selected as the experimental group was class XI IIS A with a total of 20 students, and the class selected for the control group was class XI IIS B with a total of 20 students. The results of the research show that the application of Technological Pedagogical Content Knowledge (TPACK) learning by al-Qur'an hadith teachers to the learning outcomes of al-Qur'an hadith at MAS DDI Tellu Limpoe, Sidrap Regency has increased. From the research results from samples from each experimental class and control class, it shows that the learning outcomes of the Al-Qur'an hadith from the experimental class which was given the application of Technological Pedagogical Content Knowledge (TPACK) were much higher than the control class which was not given the application of Technological Pedagogical Content Knowledge (TPACK). This is shown by the results of data analysis obtained from the experimental class and control class. The experimental class had an average pretest score of 81.05 and a posttest score with an average of 85.1, while the average pretest score of the control class was 81.00 and the posttest score was 83.15 on average. Thus, it is proven that classes with the application of Technological Pedagogical Content Knowledge (TPACK) experience increased learning outcomes compared to classes that are not given the application of Technological Pedagogical Content Knowledge (TPACK).